MILITARY-PATRIOTIC EDUCATION OF HIGH SCOOL STUDENTS IN THE CONDITIONS OF IDEOLOGICAL CONFRONTATION - Ostapenko, Olexander; Tymchyk, Mykola (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article highlights the problem of military-patriotic education of high school students in the context of ideological confrontation, which has developed as a result of the armed and information aggression of the Russian Federation against Ukraine, relevant to modern pedagogical theory and practice. The essence and purpose of the article is to cover: the current state of military-patriotic education of high school students in terms of ideological confrontation; determination and substantiation of criteria, indicators and levels of military-patriotic education of high school students in the conditions ideological confrontation; pedagogical conditions military-patriotic education of high school students in the conditions of ideological confrontation in general secondary education institutions. The study used theoretical methods (analysis, synthesis, comparison, classification, systematization, generalization), empirical methods (pedagogical observation, conversation, questionnaires and testing of high school students, pedagogical experiment (ascertaining, formative) and statistical methods were used to compare results research, elucidation of the dynamics of quantitative changes in the levels of military-patriotic education of high school students of general secondary education. The essence of the concept of “military-patriotic education of high school students in the ideological confrontation” is clarified, the reasons for the low level of military-patriotic education of high school students are the lack of desire to participate in various forms of extracurricular military-patriotic work. The vast majority of teachers of the subject «Defense of Ukraine» are part-time teachers of the humanities and physical education. Hence the problem of methodical training of teachers of the subject “Defense of Ukraine”. The scientific novelty of the researched problem is that for the first time pedagogical conditions of military-patriotic education of high school students in the conditions of ideological confrontation are developed. The practical significance of the article is that its materials can be used in organizing and conducting classes on “Defense of Ukraine”, in extracurricular and out-of-school activities on military-patriotic education, training of teachers on “Defense of Ukraine”, leaders of clubs and sections on military-applied sports and games.